Promoter hypermethylation of Wnt inhibitory factor-1 in patients with lung cancer: A systematic meta-analysis. Issue 49 (December 2016) - Zheng, Yu; Li, Xia; Jiang, Yiming; Xu, Yufen; Song, Binbin; Zhou, Qiang; Liang, Xiaodong; Yang, Xinmei
Abstract: Background: Promoter hypermethylation of Wnt inhibitory factor-1 ( WIF-1 )—a tumor suppressor gene—has been detected in several types of human tumors. However, the association between WIF-1 promoter hypermethylation and lung cancer remains to be elucidated. Therefore, we conducted this study to evaluate the clinical significance of WIF-1 promoter hypermethylation in lung cancer. Methods: A comprehensive literature search was conducted to obtain eligible studies. The combined odds ratios (ORs) or hazard ratios and 95% confidence intervals were used to estimate the strength of associations. Results: A total of 8 eligible publications with 626 cases and 512 controls were included in our study. The combined ORs revealed that WIF-1 promoter hypermethylation was significantly higher in lung cancer than in controls (OR 10.53, P < 0.001). Moreover, WIF-1 promoter hypermethylation was significantly associated with smoking behavior (OR 1.88, P = 0.002). No significant correlation was found between WIF-1 promoter hypermethylation and sex status, age status, tumor stage, and pathological types in cancer. Multivariate analysis results indicated the absence of correlation between WIF-1 promoter hypermethylation and with relapse-free survival and overall survival. Subgroup analysis by sample type demonstrated that promoter hypermethylation of WIF-1 was significantly associated with an increased risk of lung cancer in the tissue (OR 7.89, P < 0.001), blood (OR 21.83, P = 0.034), and pleural effusion subgroups (OR 157.43, P = 0.001). Conclusions: Promoter hypermethylation of WIF-1 may play a crucial role in lung cancer carcinogenesis. It may be a noninvasive biomarker using blood or pleural effusion detection. WIF-1 promoter hypermethylation is correlated with smoking behavior, but not with sex status, age status, tumor stage, pathological types, and the prognosis of lung cancer patients in terms of relapse-free survival and overall survival. More investigations, including a larger number of subjects, are required to further confirm the findings of our analysis.